2006
DOI: 10.1002/path.2067
|View full text |Cite
|
Sign up to set email alerts
|

Expression of elevated levels of pro‐inflammatory cytokines in SARS‐CoV‐infected ACE2+ cells in SARS patients: relation to the acute lung injury and pathogenesis of SARS

Abstract: The authors have previously shown that acute lung injury (ALI) produces a wide spectrum of pathological processes in patients who die of severe acute respiratory syndrome (SARS) and that the SARS coronavirus (SARS-CoV) nucleoprotein is detectable in the lungs, and other organs and tissues, in these patients. In the present study, immunohistochemistry (IHC) and in situ hybridization (ISH) assays were used to analyse the expression of angiotensin-converting enzyme 2 (ACE2), SARS-CoV spike (S) protein, and some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
390
1
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(415 citation statements)
references
References 46 publications
12
390
1
7
Order By: Relevance
“…CXCL10 may be responsible for the infiltration of activated T cells and monocytes or macrophages, which is a pathologic finding in SARS patients (41)(42)(43). It has been reported that elevated expression of monocyte or macrophage activation factors (CCL2 and CCL3) was observed in SARS patients (8,44). Furthermore, the highest expression of IL-6 in mOrVVNHis-immunized mice is reasonable (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…CXCL10 may be responsible for the infiltration of activated T cells and monocytes or macrophages, which is a pathologic finding in SARS patients (41)(42)(43). It has been reported that elevated expression of monocyte or macrophage activation factors (CCL2 and CCL3) was observed in SARS patients (8,44). Furthermore, the highest expression of IL-6 in mOrVVNHis-immunized mice is reasonable (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…He and colleagues suggested that resident ACE2-expressing lung epithelial cells, and not the subsequently recruited inflammatory cells, constitute the primary source of elevated cytokines in patients infected with SARS-CoV, and that these epithelial-derived cytokines play an important role in the acute lung injury and pathogenesis of SARS (27). Our data show that type II alveolar cells likely contribute to the high concentrations of cytokines and chemokines detected in the gas-exchange portion of the lungs in patients with SARS.…”
Section: Discussionmentioning
confidence: 99%
“…Based on in situ hybridization and immunocytochemistry, He and colleagues suggested that ACE2-positive infected cells in lungs of patients with SARS are the source of proinflammatory cytokines (27).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Cellular infiltration by macrophages has been observed, as has a combination of macrophages and lymphocytes, with or without neutrophils. 6,8,[17][18][19]48,58,69 Large multinucleated cells identified as macrophages and pneumocytes by immunohistochemistry are frequently observed in the lungs of SARS patients. Bronchiolitis obliterans organizing pneumonia, 48 hemophagocytosis in the mononuclear cells residing in pulmonary tissues, 48 and apoptosis of epithelial cells, monocytes/macrophages, lymphocytes and pneumocytes 17 are also seen.…”
Section: Pathologic Changesmentioning
confidence: 99%
“…6,19 In situ hybridization and immunohistochemistry studies have identified viral nucleic acid and/or antigen in epithelial cells from bronchi, bronchioles, trachea, and alveoli and in multinucleated cells and alveolar macrophages. 16,17,47,58,66,75 Investigation of the cytokine and chemokine profiles of SARS patients has suggested that severe SARS-related lung injury might be attributed to an excessive host immune response-particularly, the deregulation of proinflammatory cytokine production. 48,50,68,77 Wild Animals and Domestic Animals in the Market…”
Section: Pathologic Changesmentioning
confidence: 99%